ORTA ÁSIRLER TÚRKIY ÁDEBIYATÍNDA ShEShENLIK DÁSTÚRLER - Orazov, Á.O. (SCIENCE and SOCIETY, 2025)
This article analyzes the historical foundations and artistic characteristics of oratory that developed in Turkic literature between the 11th and 14th centuries. Rhetorical techniques, question-and-answer structures, proverbs, and aphorisms in the works of Yusuf Khass Hajib, Mahmud Kashgari, Ahmad Yugnaki, Khwarezmi, Sayfi Sarayi, and Qutb were examined. The role and spiritual-cultural significance of medieval written monuments in shaping the rhetorical tradition were elucidated. The article illuminates the function of oratory in transmitting folk wisdom and ethical values to future generations.